Causal atlas between inflammatory bowel disease and mental disorders: a bi-directional 2-sample Mendelian randomization study - Yang, Xiaorong; Yang, Lejin; Zhang, Tongchao; Zhang, Hong; Chen, Hui; Zuo, Xiuli (Frontiers in Immunology, 2023)
Background: The brain-gut axis link has attracted increasing attention, with observational studies suggesting that the relationship between common mental disorders and inflammatory bowel disease (IBD) may run in both directions. However, so far, it is not clear whether there is causality and in which direction. Methods: We conducted a bidirectional 2-sample Mendelian randomization study to investigate the relationship between IBD, including Crohn's disease (CD) and ulcerative colitis (UC), and mental disorders, using summary-level GWAS data. The main analysis was the inverse variance weighted method. IBD (including CD and UC), and nine mental disorders were used as both exposures and outcomes. Results: We found that UC could significantly lead to obsessive-compulsive disorder, attention deficit hyperactivity disorder, and autism spectrum disorder, with odds ratio (OR) of 1.245 (95% confidence intervals [CI]: 1.069-1.450; P=0.008), 1.050 (95%CI: 1.023-1.077; P=2.42×10-4), and 1.041 (95%CI: 1.015-1.068; P=0.002) respectively. In addition, we found that bipolar disorder and schizophrenia could increase the odds of IBD, with OR values of 1.138 (95%CI: 1.084-1.194; P=1.9×10-7), and 1.115 (95%CI: 1.071-1.161; P=1.12×10-7), respectively. Our results also indicate that obsessive-compulsive disorder could lead to IBD, especially for UC, with OR values of 1.091 (95%CI: 1.024-1.162; P=0.009), and 1.124 (95%CI: 1.041-1.214; P=0.004), respectively. Conclusions: Our findings indicate that the brain-gut axis involves the association between IBD, especially UC, and some mental disorders, which guides the targeted prevention, management, and mechanism exploration of these diseases.